QUALITATIVE AND QUANTITATIVE ANALYSIS OF ALKALOID COMPOUNDS IN LAGOCHILUS INEBRIANS BGE. (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2026)
Lagochilus inebrians Bge. is one of the valuable medicinal plants belonging to the family Lamiaceae. This plant is widely known for its biologically active compounds and has traditionally been used in folk medicine due to its sedative, hemostatic, anti-inflammatory and pharmacological properties. The chemical composition of Lagochilus inebrians includes various groups of secondary metabolites, such as flavonoids, tannins, diterpenoids, essential oils, phenolic compounds and alkaloids. Among these compounds, alkaloids are of particular scientific interest because they often show strong physiological activity even in small amounts.The present thesis is devoted to the qualitative and quantitative analysis of alkaloid compounds found in Lagochilus inebrians Bge. The study focuses on the extraction of alkaloid-containing fractions from plant material, the detection of alkaloids by specific qualitative reactions, and the determination of their total amount using analytical methods. The relevance of this research is associated with the need to study the phytochemical composition of local medicinal plants, to identify biologically active substances, and to evaluate the potential of plant raw materials as sources of natural compounds for pharmaceutical use.